A systematic review and meta-analysis of intravenous glucocorticoids for acute pain following total hip arthroplasty. Issue 19 (May 2017) - Li, Xiuhua; Sun, Zheng; Han, Chengbing; He, Liangliang; Wang, Baoguo
Abstract: Background: Glucocorticoids are increasingly used perioperatively, principally to prevent postoperative nausea and vomiting (PONV), and acute postoperative pain following total hip arthroplasty (THA). The authors hypothesized that preoperative intravenous glucocorticoids is associated with less pain scores and PONV without increasing the complications after THA. Methods: Four databases (PubMed, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science) were searched with the limitations of randomized controlled trials (RCTs). The search cutoff date was set at November 6, 2016. Participants were patients who were prepared for primary THA. Intervention was preoperative intravenous glucocorticoids for postoperative pain control. Outcomes including the visual analog scale (VAS) scores at the postanesthesia care unit (PACU) and at 24 and 48 hours post operation, the occurrence of PONV and total morphine consumption were recorded. We calculated risk ratio (RR) with a 95% confidence interval (CI) for dichotomous outcomes, and the weighted mean difference (WMD) with a 95% CI for continuous outcomes. Results: A total of 6 studies were evaluated, which included 297 patients who underwent hip surgery with intravenous glucocorticoid treatment and control patients who underwent hip surgery without glucocorticoid treatment. Pooled results indicated that intravenous glucocorticoid treatment was associated with a reduction of VAS scores at the PACU (WMD = −9.06, 95% CI −12.67 to −5.45, P  = .000) and total morphine consumption by 15.68 mg (WMD = −15.68, 95% CI −24.60 to −6.75, P  = .001). No significant difference was observed in the VAS scores at 24 and 48 hours between the intravenous glucocorticoid and placebo treatments. Intravenous steroids can decrease the occurrence of PONV (RR = 0.46, 95% CI 0.26–0.82, P  = .029). Conclusion: Intravenous glucocorticoid treatment can decrease early pain intensity and PONV after THA. However, the evidence for the use of glucocorticoids is limited by the low number of studies and variation in dosing regimens. Thus, additional high-quality RCTs are needed to identify the optimal drug protocol and determine the safety of intravenous glucocorticoids. Abstract : Supplemental Digital Content is available in the text